Challenges in Managing Public Library Services Aimed at Ensuring the Well-being of Society in the Context of Emergency Situations - Šaparnienė, Diana; Kulikauskienė, Kristina; Aleksandravičiūtė, Neringa; Miežinienė, Virginija (Social Welfare: Interdisciplinary Approach, 2024)
The paper analyses the challenges of managing public library services in the context if emergencies in order to sustain public library services and thus contribute to the well-being of society. This is done by answering the following questions: What challenges can be identified in managing public library services in emergencies? Are public libraries resilient in emergency situations? What are the main enabling and limiting factors influencing the management of public library services to ensure public welfare in such situations? Understanding the enabling and limiting factors can help to ensure the resilience of public libraries to emergency situations and support public well-being in such situations. For the empirical research the mixed methods approach is applied by conducting quantitative survey of public libraries’ staff and qualitative interviews with library managers and experts in the field of emergency situations, working in public libraries in municipalities of Kaunas and Šiauliai counties (15 municipalities). The research sample consists of 620 respondents in the quantitative study and 12 informants in the qualitative study. The empirical research has revealed that while libraries face a multitude of challenges, they are among the most resilient organizations for emergencies. Key enabling factors were identified that influence the management of public library services to ensure societal well-being during emergency situations: cross-sectoral and cross-institutional collaboration, social networks, empowering leadership, long-term strategic planning, innovativeness, knowledge and competence development, financial stability, technology development, human resource management and performance management, strategic and psychological resilience, crisis resilience and comprehensive emergency preparedness, accessibility and dissemination of information. The identified main restricting factors are: lack of resilience, inappropriate leadership, lack of funding, lack of strategy, limited human resources and their digital literacy. The implementation of enabling factors and elimination of restrictions is inseparable from the effective management of public library services in emergency situations to ensure the provision of services necessary for the well-being of society.